International Experience in Reforming and Improving the Efficiency of the Education System - qizi, Xidirova Umida Islom (Researchparks Publishing, 2023)
The principles of reforming the education system in Russia are presented. A comparative analysis of the processes of reforming the educational systems of Australia, Canada, OECD countries, as well as mechanisms for improving the efficiency of the education system is given.